The Implementation of the Madrasah Principal's Policies in Enhancing the Competence of Educators and Educational Staff of Islamic Junior High School (Perspective of the Independent Curriculum) - Dwiyono, Yudo; Tannarong, Yudhy (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to analyze the policies, implementation strategies, and influence of the policies of the Principal of the Islamic Middle School to improve the competence of educators and education staff based on the independent curriculum perspective. This research used a qualitative approach with a case study method. The informants in this research were the school principal, deputy principal for curriculum, educators/teachers, and education staff. The data was collected through in-depth interviews, observations, and documentary studies. The data analysis technique used the Miles and Huberman model with the following stages: (1) Data Collection, (2) Data Reduction, (3) Data Presentation, (4) Conclusion Drawing/Verification. Data validity used triangulation techniques, including source and technical triangulation. The results of the research show that: (1) the policies implemented by the principal of the Islamic Middle School, among others, recruitment of educators and educational staff is always adjusted to their qualifications or abilities, placement of educators and educational staff is based on competency, fostering active and communicative relationships with educators and educational staff, giving awards to educators and educational staff who excel; (2) the strategy of the principal of the Islamic Middle School includes: regular meetings, training, supervision, Subject Teacher Working Groups (MGMP), follow-up studies, and benchmarking; (3) The influence of the policy of the principal of the Islamic Middle School including increased accreditation, increased student achievement, and high public trust. The conclusion of this research is to implement the Islamic Middle School policy to improve the competence of educators and education personnel from the Independent Curriculum perspective.